RESEARCH ON THE PATH OF CULTURAL INHERITANCE AND EDUCATION OF CHINESE MEDICINE IN VOCATIONAL COLLEGE UNDER THE PERSPECTIVE OF CRAFTSMANSHIP - Huizuo, Zhai (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
Through investigation and research, a deep understanding of the contemporary connotation of traditional Chinese medicine culture of craftsmanship is gained. The current situation of the understanding of craftsmanship by teachers, students, and enterprises, which includes insufficient understanding, lack of professional integration, integration of industry and education in a formal manner, and lack of a craftsman-type teaching team, is also analyzed. In the end, it is concluded that the targeted countermeasures are to combine with the campus culture construction, hold and participate in traditional Chinese medicine skills competitions, set up more Chinese medicine special skills courses, carry out the reform of the curriculum and teaching mode, and adhere to and carry forward the "artisanal spirit" in the training of teachers, to provide practical guidance for the cultivation and inheritance of the craftsmanship spirit of the traditional culture of traditional Chinese medicine.